ナンキョク オアシス ニ オケル タイセキブツ スイシリョウ チュウ ノ ビリョウ ゲンソ ノ ブンプ ニ カンスル チキュウ カガクテキ ケンキュウ ソノ1 DVDP13 コアー シリョウ オヨビ ベスト フォールド ヒルズ ノ タイセキブツ チュウ ノ RA ノ ガンリョウ - 堀内, 公子; ホリウチ, キミコ; 鳥居, 鉄也; トリイ, テツヤ; 村上, 悠紀雄; ムラカミ, ユキオ; HORIUCHI, Kimiko; TORII, Tetsuya; MURAKAMI, Yukio (国立極地研究所, 1977)
P(論文) ドライバレー地域の掘削で得られたDVDP 13コアー試料とベストフォールド・ヒルズの湖底堆積物について,過塩素酸可溶部と不溶部の炭酸ナトリウム融解抽出部のそれぞれの中のRa量を求めた.Raの定量は放射平衡に達したRnを液体シンチレーションカウンターで測定した.BGが45 cpmのとき,その1/8を測定下限とすると,2gの試料で0.25±0.04×10^<-12> Ci/g のRaの測定が可能である.UとThとの地球化学的な行動が異なることに基づいて考察すると,Uは海水で運ばれ,生成した^<230>Thが沈積しやすく,娘核種の^<226>Raとは一万年弱で放射平衡に達する.放射平衡に達するまで^<226>Raの量は次第にふえ,それから7.5×10^4年の半減期で減少していく.ゆえに過塩素酸可溶部と炭酸ナトリウム融解部のRaを定量することにより,堆積生成以来のおよその年代の古さを知り得る.ドライバレー地域では前者の値が後者より数倍も多く今回の試料中で最も古く,スチニア湖湖底堆積物は最も新しいと推定した. The ignition loss and the Ra content in the 10% HClO_4-soluble fraction and Na_2CO_3-fusion fraction were respectively determined for the 17 core samples (DVDP 13 core), down to the depth of 50 meters and for the four lake deposits in the Vestfold Hills. The determination of Ra was performed by measuring the activity of Ra in radioactive equilibrium state with a liquid scintillation counter. The detection limit of Ra with 2 grams of sample wag (0.25±0.04)×10^<-12> Ci/g, taking one-eighth of the BG counting rate, 45 cpm, as the limit in this case. Based on the differences between U and Th in geochemical behaviors, it is thought that U is transported into sea water and decays to ^<230>Th which tends to precipitate in the site. From ^<230>Th is produced ^<226>Ra which attains the radioactive equilibrium within a little under ten thousand years. And then, the ^<226>Ra content gradually increases with a half life of 7.5×10^4 years. Therefore, by determining the ratio of Ra in the HClO_4-soluble fraction to that in the Na_2CO_3-fusion fraction of a sample, it is possible to determine its age since the time of sedimentation. The results obtained indicate that the Dry Valley sediment is the oldest while the Lake Stinear sediment is the latest because the ratio is the largest for the former and the smallest for the latter. departmental bulletin paper